Propuesta de mejora en los procesos de distribución y almacenamiento de una empresa distribuidora de materiales de construcción - Quispe Ayuque, Miguel Angel (2024)
This study proposes an integrated solution to enhance the distribution and storage processes of a construction materials distributor in Huancavelica. The primary issue identified is significant non-compliance with delivery times, which has led to a decrease in customer satisfaction and an increase in operational costs due to the subcontracting of transportation and management of sales returns. According to the analysis, over 30% of shipments experience delays, directly impacting profitability and customer experience. These delays have not only caused financial losses but also a reduction in customer loyalty, as clients seek more reliable options for construction materials supply. To address this issue, several alternatives were evaluated, including the implementation of an ERP system, the purchase of light cargo vehicles, and the incorporation of a hoisting solution to optimize the loading and unloading process. Each solution was assessed based on cost, efficiency, and ease of implementation. Ultimately, a solution comprising three key components was selected: the implementation of a cloud-based ERP system to centralize order and stock information, the redesign of distribution processes, and the purchase of two light cargo vehicles to reduce dependence on heavy cargo fleets. This approach will provide greater flexibility and the ability to access areas with difficult access, ensuring delivery times are significantly reduced.